Risk and protective factors for sudden infant death syndrome (SIDS) in low-resource communities in Kolkata India: a mixed methods exploratory study of semi-structured interviews and survey data - Samreth, Susan; Leader, Alexandra; Kiely, Jillian; Chakrabarti, Turja; Kapoor, Rupa (Frontiers in Pediatrics, 2025)
Sudden Unexpected Infant Death (SUID), Sudden Infant Death Syndrome (SIDS) and infant sleep practices are widely documented and studied in high-resource countries. Knowledge of SUID/SIDS occurrence, risk factors and protective factors in low or middle-resource countries such as India is lacking. This was an exploratory study using a mixed methods (qualitative and quantitative) approach to better understand infant sleep practices and the various factors that may influence them amongst caregivers in 5 low-income communities in Kolkata, India. Twenty-eight and 22 caregivers of infants <12 months old were recruited using a convenience sampling approach to participate in semi-structured interviews (phase 1) and a survey (phase 2), respectively. This research was conducted in partnership with Pratit International, a locally based NGO dedicated to providing comprehensive health care to disenfranchised communities in Kolkata. Analysis of qualitative and quantitative data found that infant caregivers frequently described risk factors (e.g., bedsharing, soft sleep surface, infant sleep position, objects in sleep area, environmental smoke exposure, low rates of pacifier use) and protective factors (e.g., breastfeeding, routine immunization/prenatal care, low rates of caregiver substance use) that have been associated with SIDS in high resource communities. Qualitative data revealed that certain caregivers' reasons for infant sleep position were rooted in cultural beliefs. Prenatal and postnatal sleep education given by a healthcare professional were limited and awareness of safer sleep advice in the community was low. These study findings suggest the need to provide safer sleep education resources in a culturally appropriate manner and can help guide future research on potential interventions such as the baby box.